Single Cell Transcriptomics of Ependymal Cells Across Age, Region and Species Reveals Cilia-Related and Metal Ion Regulatory Roles as Major Conserved Ependymal Cell Functions - MacDonald, Adam; Lu, Brianna; Caron, Maxime; Caporicci-Dinucci, Nina; Hatrock, Dale; Petrecca, Kevin; Bourque, Guillaume; Stratton, Jo Anne (Frontiers in Cellular Neuroscience, 2021)
Ependymal cells are ciliated-epithelial glial cells that develop from radial glia along the surface of the ventricles of the brain and the spinal canal. They play a critical role in cerebrospinal fluid homeostasis, brain metabolism, and the clearance of waste from the brain. These cells have been implicated in disease across the lifespan including developmental disorders, cancer and neurodegenerative disease. Despite this, ependymal cells remain largely understudied. Using single-cell RNA sequencing data extracted from publicly available datasets, we make key findings regarding the remarkable conservation of ependymal cell gene signatures across age, region and species. Through this unbiased analysis, we have discovered that one of the most overrepresented predicted ependymal cell functions relates to a critically understudied role in metal ion homeostasis. Our analysis also revealed distinct subtypes and states of ependymal cells across regions and age of the nervous system. For example, neonatal ependymal cells maintained a gene signature consistent with developmental processes such as determination of left/right symmetry; while adult ventricular ependymal cells, not spinal canal ependymal cells, appeared to express genes involved in regulating cellular transport and inflammation. Together, these findings highlight underappreciated functions of ependymal cells, which will be important to investigate in order to better understand these cells in health and disease.